Kidney allograft dysfunction due to ipsilateral thigh arteriovenous graft. Issue 5 (September 2020) - Agrawal, Nikhil; Garg, Neetika; Adapa, Sreedhar; Cardarelli, Francesca
Arteriovenous graft in the thigh is used not infrequently for hemodialysis. Outcomes with this lower extremity dialysis access are generally comparable to upper extremity access and superior to long-term catheter use. However, it could have significant implications in a patient getting a kidney transplant. Here we describe a case of thigh arteriovenous graft causing kidney allograft dysfunction in a new transplant recipient, and this resolved with graft ligation.